Material aspects of the law-making competence of communes in the light of the amendedAct on upbringing in sobriety and counteracting alcoholism - Lewicki, Marek (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The aim of the article is to present and analyse some selected aspects of changes in the area of law-making competence of communes [gmina] under the Act on upbringing in sobriety and counteracting alcoholism. It should be emphasized that these competences are the key instruments to achieve the objectives of this act, hence every change in the law in this area requires special attention. The article attempts to determine the possibilities resulting from the applicable law, but at the same time to determine some limits in the shaping of the content of law-making decisions taken by the commune authorities based on the authorizations included in the Act.